IMPLEMENTING QUICK RESPONSE (QR) CODES IN TEACHING READING - Hapsari, Suci; Nur Ekawati, Yulia; Molla, Nur Laila (LPPM Universitas Pancasakti Tegal, 2019)
The purposes of this research were to describe the implementation of Quick Response (QR) Codes in teaching reading, to find out the significant difference between students who are taught with and without using QR Codes, and to know the students? responses from using QR Codes in teaching reading of English explanation texts to XI class in MAN Kota Tegal in the academic year of 2018/2019. This research used a type of experimental study with pretest-posttest control design. The results of the study described the QR Codes could be implemented in teaching reading as a teaching medium. The steps of applying this medium were (1) asking students to make a group, (2) scanning the QR Code to get reading text and worksheet of assignment, (3) doing the activities stated in QR codes, and lastly (4) discussing the result. Moreover, t-test result showed higher than t-table (4.372 > 2.011). It meant that there was significant difference from experiment and control group. In accordance with students? responses result, it mentioned that students felt enthusiastic, motivated, and discovered new things during teaching learning process through QR Codes. Therefore, it was suggested to English teacher using QR Codes in teaching reading.